Sutika Paricharya: An Overview. - Paijwar, Priya; Awasthi, H H; Mishra, Deepa (International Research Journal of Ayurveda & Yoga, 2023)
According to Acharya Kashyapa, woman is termed as Sutika only after the delivery of foetus with its placenta. In Ayurveda Samhitas duration of Sutika Awastha is one and half month after delivery of baby followed by expulsion of placenta. In this period puerperal women become weak and lethargic, because of labor pains and blood loss during delivery. In Ayurveda, weakness in Sutika said to be occurred due to Garbhavriddhi and Shoonyasharir. Causation of Sutika Roga is Agnibala Mandya. Therefore, Ahara of Sutika should be properly managed. Acharyas of different treaties have described Sutika Paricharya into two categories; Samanya Sutikaparicharya and Vishishta Sutikaparicharya, Pathya and Apathya along with specific Aushadha Yogas. Acharya Kashyapa has mentioned special regimen for Sutika. It causes Agni Balavriddhi which is responsible for Dhatupushti. To prevent Sutikaroga proper care of Ahara and Vihara of Sutika is vital. This care is termed as Sutika Paricharya.